Análise dialógica e argumentativa de letras de músicas de Chico Buarque - Costenaro, Silvane (2009)
The present work analysis lyrics from Chico Buarque de Holanda, composed in the military dictatorship peiod (1964-1985). The analyses have as theoretical support some of the linguistic ideas of Bakhtin Circle and the Theory of Argumentation in the language from Ducrot and contributors. From the vast bakhtin legacy, it is evidenced the socioideological character of the language. Initially, Theory of Argumentation in language, phases are explicit, emphasizing the current phase, the theory of semantic blocks. Aiming to verify the relation that can be established between these two theories, the concepts of Dialogic (al) theory are then exposed afterwards. They are presented separately in the way as the analysis. The argumentative reading possibles an intralingüístic analysis and dialogical one, in turn, possibles an extralinguistic. Concluding this study, we can say that these two theories complement and enrich the analysis, once the argument (teory) works with the linguistic-discursive marks, reaching the context automatically, even though it is not the object of study of this theory, but it is (object) from dialogic, which considers the extraverbal the starting point